INTER-SUBJECT RELATIONS OF THE RUSSIAN LANGUAGE AND METHODS OF THEIR IMPLEMENTATION IN EDUCATIONAL WORK - Махмудбекова Гулнора Убайдуллаевна (Journals Park Publishing, 2024)
This article examines the interdisciplinary connections of Russian language and the methods of their embodiment in learning activities. It explores how the Russian language is interwoven with various academic subjects, providing a deeper understanding of language skills in different areas of knowledge. The article presents specific methods for implementing cross-curricular connections, such as analyzing literary works to study language trends, examining historical documents to identify linguistic changes over time, and using computational methods to analyze data on large amounts of text.
Keywords: Interdisciplinary links, Integrated approach, Linguistic analysis, Historical perspective, Sociolinguistics, Cognitive aspects of language, Computer linguistics, Innovative teaching methods.